Pendidikan Kesehatan Dengan Media Menarche Flashcard Islami Tentang Menarche Terhadap Tingkat Pengetahuan Dan Kecemasan Siswi - Amadeaz, Ivanica Anggi; Hikmawati, Isna; Aprilina, Happy Dwi; Muzaenah, Tina (Fakultas Kesehatan Masyarakat, Universitas Diponegoro, 2023)
Adolescence is a transitional period from childhood to adolescence. Menarche is the first menstruation experienced by adolescents at the age of 10-16 years. Anxiety about menarche is anxiety in adolescents caused by a lack of knowledge about menarche. The purpose of this study was to determine the effect of health education using Islamic menarche flashcard media on the level of knowledge and anxiety in facing menarche. Quantitative research method pre-experimental one-group-pretest-posttest design. The population and sample used amounted to 50 respondents with the total sampling method. The statistical test used is the Wilcoxon test. The results showed that the level of knowledge before the intervention was 56.08 and after the intervention the score increased to 90.28. The result of the anxiety level before the intervention was 30.40 and after the intervention the score decreased to 16.40. The conclusion is that there is an influence by providing health education with Islamic menarche flashcard media to increase knowledge and reduce student anxiety in facing menarche.